2020
DOI: 10.1080/09273948.2020.1716024
|View full text |Cite
|
Sign up to set email alerts
|

Tear Mediators NGF along with IL-13 Predict Keratoconus Progression

Abstract: Purpose: To find immunomediator combinations which could sensitively indicate keratoconus progression. Methods: Tear samples of 42 patients with keratoconus were collected at baseline and at the end of a one-year follow-up. The concentrations of 13 mediators were measured by CBA. Based on Pentacam HR examination, eyes were divided into a non-progressive and a progressive group. Results: At the end of the follow-up, significant differences were observed in the release of IFNγ, IL-13, IL-17A, CCL5, MMP-13 and PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…IL-1β, IL-6, IL-17A, TNFα, IFNγ, IgE, MMP2, EPO, PDGF-BB, sVCAM, sL-selectin, granzyme-B and perforin were observed to be significantly increased compared to controls in two or more of KC grades. This finding is consistent with earlier observations reporting increased levels of IL-1β 26 , 40 42 , IL-6 24 , 26 , 30 , TNFα 41 , IL-17A 40 , 43 , IFNγ 44 and MMP2 26 in the tear fluid of KC patients. The observed variation in tear fluid expression of MMP9 24 33 , 45 , IL-8 26 , 33 , 46 , IL-13 40 , IL-21 40 , IL-23 40 , IFNα 40 , MCP1 40 and CCL5 31 , 32 , 44 between the current study and previous reports, may be attributed to differences in sample size and stage of KC investigated in the cohort.…”
Section: Discussionsupporting
confidence: 93%
“…IL-1β, IL-6, IL-17A, TNFα, IFNγ, IgE, MMP2, EPO, PDGF-BB, sVCAM, sL-selectin, granzyme-B and perforin were observed to be significantly increased compared to controls in two or more of KC grades. This finding is consistent with earlier observations reporting increased levels of IL-1β 26 , 40 42 , IL-6 24 , 26 , 30 , TNFα 41 , IL-17A 40 , 43 , IFNγ 44 and MMP2 26 in the tear fluid of KC patients. The observed variation in tear fluid expression of MMP9 24 33 , 45 , IL-8 26 , 33 , 46 , IL-13 40 , IL-21 40 , IL-23 40 , IFNα 40 , MCP1 40 and CCL5 31 , 32 , 44 between the current study and previous reports, may be attributed to differences in sample size and stage of KC investigated in the cohort.…”
Section: Discussionsupporting
confidence: 93%
“…An increase in tear levels of IFN-gamma is associated with disease progression and corneal thinning. [ 89 ] Epithelial TNF-α levels from the cone region have a positive association with Belin–Ambrosio-enhanced ectasia display scores, corneal deformation, and keratometry, all of which suggest a biomechanical weakening process. [ 44 ] TGF-β tear levels indicate a profibrotic state and an increase in the tear levels correlates with corneal remodeling and scarring in advanced KC.…”
Section: Nflammatory M Arkersmentioning
confidence: 99%
“…Another study found higher levels of innate biomarkers, namely toll-like receptors 2 and 4, on the ocular surface of subclinical keratoconus patients, and drawing from this finding, the authors advocated their use as a biomarker in identifying keratoconus cases. 19 Interestingly, Fodor and colleagues 20 demonstrated that a concomitant increase in tear nerve growth factor and interleukin (IL)-13 predicts keratoconus progression with a sensitivity and specificity of 80% and 100%, respectively.…”
Section: Advances In Diagnosismentioning
confidence: 99%